Analysis of Teaching Material Development for Islamic Education Teaching Methodology Based on 6C'S - Asri Karolina; Reni Melawati; Rahmad Hidayat; Aini Syahira Jamaluddin (Ta'dib: Jurnal Pendidikan Islam, 2022)
The purpose of this study is to determine the instructional development procedures and the development of the teaching methodology of Islamic Education based on 6Cs. This study uses a qualitative method with a qualitative descriptive approach. The results of this study indicate that first, the results of the analysis of the procedures for developing Islamic Education (PAI) teaching materials have been adjusted to the procedures for developing initial materials starting from needs analysis, design, development, evaluation, and revision. Second, analysis of how the material development is adjusted to each indicator of 6Cs (critical thinking, creative thinking, integration, communication, compassion and computer logic). Before the development of teaching materials, a starting of starch was carried out, by adjusting the curriculum material and making lesson plans. Development of teaching materials containing materials, media and assignments/projects that support the development of 6Cs abilities.